Environmental learning student’s worksheet of air pollution (eswopol): inovasi lembar kerja siswa berbasis hots-aep - Ilmi Zajuli Ichsan; Diana Vivanti Sigit; Henita Rahmayanti; Agung Purwanto; Nur Fadli Hazhar Fachrial; Tri Suwandi; Ahmad Ali; Titin; Farah Muthi Hermawati (Biology Education Department, Universitas Insan Budi Utomo, Malang, Indonesia, 2020)
Environmental problems need to be solved by students' HOTS abilities. This research aimed to develop environmental learning student's worksheet of air pollution (eswopol) based on Higher Order Thinking Skills Assessment based on Environmental Problems (HOTS-AEP). The research method used research and development that modified from Borg and Gall model. The study was conducted in December 2019 until January 2020. The research instrument used the interview transcript and validation questionnaire. The research data obtained in the form of an average score of validation results. The data analysis technique used is descriptive. The results showed that the environmental learning student's worksheet of air pollution (eswopol) based on HOTS-AEP was declared valid with an average validation score of 3.55 (very valid category). The conclusion of this research is eswopol based on HOTS-AEP is appropriate for use in a learning environment